The impact of the COVID-19 pandemic on the stock liquidity on the Warsaw Stock Exchange - Tuszkiewicz, Marcin (Journal of Finance and Financial Law, 2022)
The aim of the article is to verify the impact of the COVID-19 pandemic on stock liquidity on the Warsaw Stock Exchange (WSE). In addition the article tries to assess whether the WIG20 index includes companies with the most liquid quotations. The research was based on an analysis of transaction data of 366 companies listed in the continuous system on the WSE within the January 13–May 15, 2020 period. The analysis was performed using four liquidity measures: average number of transactions per session, average transaction value, average percentage change between transactions, average time distance between transactions in seconds. In order to specify the group of shares with the highest liquidity, a taxonomic analysis was performed using the k-means method. Results indicate that during the stock sell-off related to the COVID-19 pandemic and directly after the period of market declines, the liquidity of shares of companies listed on the WSE increased, and in each of the analyzed periods, the WIG20 consisted of the most liquid companies. Previous studies have not analyzed this phenomenon, and the results allow researchers to better understand the behavior of investors during stock market shocks.